Integrative analysis of morphological, molecular, and chemotaxonomic traits in Hyacinthella species - Erez, Mehmet Emre; Acar, Mehmet; Kalmer, Ayşenur; Eroğlu, Hüseyin (Phytotaxa, 2026)
Plant systematics encompasses not only classical taxonomic tasks but also the study of biological processes, natural variation, speciation, and reproductive biology. Morphological, phytochemical, and molecular characteristics assessed relationships and cluster analysis of Hyacinthella species.The data obtained revealed 11 morphologically distinctive characters and the presence of 56 different phenolic compounds in leaf methanol extracts. Furthermore, 3 different phylogenetic regions were amplified for 11 Hyacinthella species. Based on Principal Component Analysis, the Unweighted Pair Group Method, and the Bayesian Inference method for DNA sequences, H. siirtensis and H. nervosa were closely positioned, which indicates geographical proximity. Presence of quinic acid in all species was considered a potential key indicator for Hyacinthella species. H. siirtensis and H. nervosa were found in proximity in both morphological and chemotaxonomic aspects. In the phylogenetic analysis, the regions were analysed both individually and in combination to form trees. In the matK phylogram, H. heldreichii, H. micrantha, H. siirtensis, and H. venusta were grouped . The species H. campanulata, H. nervosa, and H. siirtensis formed a group in the terminal part of the tree with a PP value of 0.98 in the combined tree. We aimed to combine accurate and reliable diagnostic methods by analyzing different distinguishing characteristics. Our findings underscore the importance of integrating morphological, chemotaxonomic, phylogenetic data for comprehensive and accurate diagnostic studies. Ideally, a description should be as comprehensive as possible.